2019
DOI: 10.1097/sla.0000000000003270
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of Survival After Neoadjuvant Treatment and Resection for Initially Unresectable Pancreatic Cancer

Abstract: Objective: To evaluate the impact of clinical and pathological parameters, including resection margin (R) status, on survival in patients undergoing pancreatic surgery after neoadjuvant treatment for initially unresectable pancreatic ductal adenocarcinoma (PDAC). Background: Prognostic factors are well documented for patients with resectable PDAC, but have not been described in detail for patients with initially unresectable PDAC undergoing resection af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
142
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(151 citation statements)
references
References 43 publications
9
142
0
Order By: Relevance
“…Metastatic site, decreased CA19-9 level, and performance status are not significant predictive factors for early recurrence. Several articles have reported that decreased CA19-9 levels after multimodal therapy represent a reliable predictive factor for resectability, OS, and DFS [21,[29][30][31][32][33][34][35]. In most patients of the present study, CA19-9 decreased to within normal limits after multimodal treatment.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Metastatic site, decreased CA19-9 level, and performance status are not significant predictive factors for early recurrence. Several articles have reported that decreased CA19-9 levels after multimodal therapy represent a reliable predictive factor for resectability, OS, and DFS [21,[29][30][31][32][33][34][35]. In most patients of the present study, CA19-9 decreased to within normal limits after multimodal treatment.…”
Section: Discussionsupporting
confidence: 56%
“…However, early recurrence was observed in almost 20% of patients, in line with the findings of Wright et al, who reported that seven out of 23 patients (30.4%) with metastatic PDAC who underwent CS experienced early recurrence. Other studies have also reported early recurrence rates after conversion surgery of approximately 30% [27][28][29]. This would suggest that patients cannot be expected to survive longer than patients who receive non-surgical treatment, and conversion surgery may be harmful to patients because of the high risk of mortality and morbidity associated with extensive pancreatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Eight of them found that decreased CA19‐9 level was a prognostic factor for OS . Three articles found that CA19‐9 response was a prognostic factor for PFS …”
Section: Resultsmentioning
confidence: 99%
“…Even with surgery in a resectable tumor, the number of R0 resections (no tumor tissue in the respective margins) remains to low [43,44]. Pancreatic cancer has a poor prognosis, and the importance of cell residuals is outlined by the median survival that drops from 25.1 months (for R0) to only 15.3 months with R1 resection [16]. A combination with plasma treatment might become an additive approach to existing surgical and chemotherapeutic strategies to tackle the tumor cell residuals at the surgical margins of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Disseminated tumor growth induces organ dysfunction and often hinders surgical resection [12][13][14][15]. Especially in pancreatic cancer, the disseminated spread into the peritoneal cavity (peritoneal carcinomatosis) hinders successful cancer therapies [16][17][18][19][20][21][22][23]. Therefore, this type of cancer is a challenging but ideal model to investigate the effect of a novel treatment on cellular detachment and metastatic phenotype.…”
Section: Introductionmentioning
confidence: 99%